Consumer Snacking Behavior: A Survey of Biscuit Consumption Patterns - Abu Seman, Noor Aslinda; Amir Zakwan Mansor; Arifha Mohamad; Muhammad Asyraf Hasim; Nurazwa Ahmad; Mohd Asmadi Mohd Angsor (JBS Nexus, 2024)
The increasing prominence of snacking has notably influenced consumer behaviour, with biscuits being a favoured snack choice. This research examines consumer preferences for biscuit consumption, emphasising package size, consumption frequency, and time. A poll of 106 respondents indicated that 95.3% like eating biscuits, with more than half consuming them 2-3 times weekly. The research indicates a significant inclination towards smaller packing sizes, with 52.4% preferring small packs for ease and portion management. Afternoon consumption was the predominant choice, with 70.8% of respondents selecting this time for snacking. 62.3% of respondents acquire biscuits during festivals, underscoring their cultural importance during special events. The results indicate that producers might customise product offers by emphasising smaller, resealable containers to preserve freshness and promote frequent purchasing. Marketing strategies can capitalise on the solid afternoon snack preference and the surge in festival demand. This research provides valuable insights for biscuit producers and marketers to better align their products with consumer behaviour, addressing everyday and festive consumption trends. Future studies should explore demographic influences on biscuit preferences and consider the role of health-conscious consumers in shaping the market.